Design Defects and Quality of Government Funded Building Projects In Isiolo County, Kenya - Dr. Cavens Kithinji, Mbijiwe Lawrence Kinyua, Kiarie Antony Kimemia, (International Journal of Scientific Research and Management (IJSRM), 2017)
The Interface between design and pre-construction of government funded buildings projects is pivotal and yet very complicated. It is at this interface that defects emanating from design errors in the buildings have been found to occur adversely influencing the realization of quality buildings. This study investigated the influence of design defects on the quality of government funded building projects in Isiolo County. The study is guided by one theory; The Bad Apple Theory of human error. Descriptive survey research design is adopted. Study’s target population consisted; 137project clients, 92 contractors and 16 consultants. 149 respondents made up the study’s sample size and final subjects selected using Stratified and Simple random sampling techniques. Primary data was collected using three questionnaires. The analysis of quantitative data was achieved making use of descriptive statistics and qualitative data on the other hand was reported in form of narratives pivoted on themes under study. The study established that poor functionality of building parts, buildings’ fragility, high occurrence of unpleasant aesthetics in buildings and cost overruns were all as a result of design defects. This study concluded that design defects to a great extent influenced the quality of government funded building projects in Isiolo County. The study recommends that a design review involving project clients and consultants prior to the approval of the final design for construction should beunder taken. Further, to address design defects architectures should provide clear graphic and written representations which will allow contractors to transform concepts into physical reality in execution of government funded building projects in Is iolo County.